The gift of one day : how to find hope when life gets hard - Shook, Kerry; Shook, Chris (WaterBrook, 2020)
"Kerry and Chris Shook's grandson, Jude, lived for only one day after he was born. That one day changed the way they now live every day. Now they share their lessons of faith and hope. As they recount the compelling true story of Jude's short but inspiring life, Kerry and Chris reveal the transformative insights they learned when tragedy struck their family. Told with humility and transparency, their story illustrates the goodness of God even in overwhelming circumstances as they share answers to the question: How do we live each day with attentive hope when life is often so crushingly hard?"--